2022
DOI: 10.3897/natureconservation.47.71864
|View full text |Cite
|
Sign up to set email alerts
|

The effect of habitat reduction by roads on space use and movement patterns of an endangered species, the Cabrera vole Microtus cabrerae

Abstract: Roads are among the most widespread signs of man’s presence around the globe. From simple low traffic trails to wide and highly used highways, roads have a wide array of effects on wildlife. In the present study, we tested how habitat reduction by roads may affect the space use and movement patterns of the Cabrera vole (Microtus cabrerae), a near-threatened Iberian endemism, often living on road verges. A total of 16 voles were successfully radio-tracked in two habitat patches with different size and proximity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Roads were a behavioural barrier to the movement of small-sized carnivores, although they also take advantage of road proximity as feeding areas (Ferreira et al 2022). In another study, Fernandes et al (2022) also found Cabrera voles (Microtus cabrerae), an endangered small mammal, had different space use and movement patterns when living on road verges compared to living away from the road. Both studies highlight the need to integrate species behaviour into road permeability projects.…”
Section: About This Collectionmentioning
confidence: 96%
“…Roads were a behavioural barrier to the movement of small-sized carnivores, although they also take advantage of road proximity as feeding areas (Ferreira et al 2022). In another study, Fernandes et al (2022) also found Cabrera voles (Microtus cabrerae), an endangered small mammal, had different space use and movement patterns when living on road verges compared to living away from the road. Both studies highlight the need to integrate species behaviour into road permeability projects.…”
Section: About This Collectionmentioning
confidence: 96%